Oxaliplatin-induced neuropathy: a long-term clinical and neurophysiologic follow-up study - Kokotis, Panagiotis; Schmelz, Martin (Clinical colorectal cancer and other gastrointestinal malignancies, 2016)
Background - Oxaliplatin is an effective drug used mainly for advanced colorectal cancer. Neurotoxicity is the major side effect of oxaliplatin. The present clinical and neurophysiologic study was conducted to evaluate patients receiving oxaliplatin therapy. - Patients and Methods - Thirty-one consecutive patients with colorectal cancer who received oxaliplatin therapy were followed up for more than 3 years. The patients underwent clinical and neurophysiologic tests for large and small fiber function at every visit. - Results - Most of the patients received oxaliplatin-based chemotherapy at the initial dose of 130 mg/m2 for 6 to 8 cycles, normally every 3 weeks. Acute neurotoxicity with cold and mechanical hyperalgesia was reported by the vast majority of patients after each cycle of therapy and was confirmed by the quantitative sensory, filament, and axon reflex test. Chronic sensory cumulative neuropathy developed in most of the patients after the middle of therapy with numbness and was assessed using clinical scales, nerve conduction studies, and the vibration threshold. Our results support the persistence of the sensory nerve deficits for years after cessation of oxaliplatin therapy. - Conclusion - Our study has confirmed the results of a few previous long-term studies concerning the persistence of chronic large sensory fiber neuropathy and the influence of the cumulative dose of oxaliplatin on the development and severity of the chronic neuropathy. Our findings have improved the knowledge about the acute oxaliplatin-induced neurotoxicity using the C-fiber axon reflex response.
Gesehen am 12.12.2019
Available online 27 February 2016